The Application of Party Autonomy Principle in Arbitration - Novian, Desri (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2024)
The application of both substantive and procedural law should be imperative, however, in arbitration, there is a concept that substantive and procedural laws that are imperative in the place (country) where the arbitration is held or where the arbitration award is enforced can be waived by the agreement of the parties which is known as the principle of party autonomy. The principle of party autonomy is interpreted as the freedom of the parties to determine the substantive and procedural law to be used in the arbitration process that arises between them based on the arbitration agreement. However, the act to waive the imperative law can cause problems in the future when the award will be enforced. Hence, this research aims to analyze the party autonomy principle based on the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958 New York Convention), UNCITRAL Model Law on International Commercial Arbitration (With amendement as adopted in 2006), Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, Civil Code (KUH.Perdata), Rules of Civil Procedure, Staatsblad (Rv), Het Herziene Indonesisch Reglement (HIR), Rechtsreglement Buitengewesten (Rbg), as well as the Principle on Choice of Law in International Commercial Contracts, by using normative legal research method. The research finds a concept that the principle of party autonomy is limited by restrictions established based on laws of the country where the arbitration is held or where the arbitration award is enforced (limited party autonomy).